Exploring the critical success factors (CSFs) for enterprise competitiveness in crises: A bibliometric review - Hamdouna, Muntaser (Research Papers in Economics and Finance, 2025)
This paper examines the evolution of research on critical success factors (CSFs) that enhance competitiveness during enterprise crises. Crises include economic recessions, financial shocks, pandemics and global disruptions. A bibliometric analysis of Scopus-indexed literature from 1998 to 2024 was conducted to address influential authors, key journals, themes and countries. Excel was used to perform statistical analysis, while VOSviewer was used to visualise the authors’ keywords in a network. The study focuses on the fields of business, economics and finance, emphasising their critical role in steering turbulent markets. The findings indicate a significant increase in research related to the CSF of enterprise competitiveness during major disruptive events, particularly during economic and financial crises. Countries such as the UK, China, Malaysia and India rank among the top publisher countries. Major themes focus on business resilience, supply chain continuity and organisational agility as core pillars for enterprises to maintain their competitiveness. Although this article relied on the Scopus database, its findings remain valuable, providing a solid foundation for future research. This study serves as a guide for experts, managers and policymakers on evidence-based strategies – such as risk management, dynamic capabilities and leadership agility (...).